The Effects of El Rondo and Passing Circuit Training on Improving Passing Accuracy Among 15–16-Year-Old Players at the Bassura Muda Futsal Academy - Rodearni Purba (CV Abid Abadi Jaya, 2026)
This study aimed to examine the effects of El Rondo and Passing Circuit training methods on improving the passing accuracy of players at the U16 Bassura Muda Futsal Academy. The study employed a quantitative approach using an experimental research design. The sample consisted of 30 players from the aged15-16 years Bassura Muda Futsal Academy, who were divided into two groups of 15 players each. Data were collected through a passing accuracy test administered before (pretest) and after (posttest) the training program. The data were analyzed using normality tests, homogeneity tests, paired-sample t-tests, and independent-sample t-tests with the assistance of SPSS software. The findings revealed that the El Rondo training method had a significant effect on improving passing accuracy, with a t-value of 6.812 and p < 0.05. Similarly, the Passing Circuit training method significantly improved passing accuracy, yielding a t-value of 9.660 and p < 0.05. The mean posttest score of the El Rondo group was 5.27, while the Passing Circuit group achieved a mean score of 5.80. Furthermore, the independent-sample t-test produced a t-value of 1.300, a t-table value of 2.048, and a significance value of p = 0.204 (p > 0.05), indicating no statistically significant difference between the two training methods. Therefore, it can be concluded that both El Rondo and Passing Circuit training methods are effective in improving the passing accuracy of U16 Bassura Muda Futsal Academy players, although neither method was found to be significantly more effective than the other.